Analysis of the Influence of Mobile Phone (Gadget) Use on Children's Students' Interest in Learning - Alim, Nur; Maharatu, Andi Puan; Andriani, Putri (Educia Journal, 2025)
This study explores the influence of mobile phone use on students' interest in learning, distinguishing between educational and recreational uses of mobile devices. A total of 300 students participated, with data collected through surveys assessing their mobile phone usage patterns and interest in various academic subjects. Descriptive statistics, Pearson correlation, multiple regression, and ANOVA analyses were employed to examine the relationship between mobile phone use and students' academic engagement. The results revealed a positive correlation between educational mobile phone use and increased interest in learning, particularly in subjects such as mathematics and science. In contrast, recreational use of mobile phones was negatively associated with students' interest in academic subjects, highlighting the potential distractions posed by non-educational mobile activities. Age was found to positively influence interest in learning, while gender did not significantly affect the outcomes. The study contributes to the literature by addressing gaps in understanding the differentiated impacts of mobile phone use, providing practical insights for educators and policymakers on how to effectively integrate mobile technology into educational settings while mitigating potential distractions. The findings suggest that mobile phones, when used for educational purposes, can enhance students' academic motivation, but their recreational use should be managed to prevent disengagement from learning.